Insecticidal activity of different fractions of petroleum ether extract of Zingiber cassumunar rhizome against Tribolium castaneum - Talukder, D; Haque, AB MH; Zaman, S; Islam, MS; Islam, MN; Khatun, A (Bangladesh Journal of Scientific and Industrial Research, 2015)
An experiment was carried out to investigate the efficacy of contact toxicity of different fractions of petroleum ether extract of Zinziber cassumunar Roxb. rhizome against Tribolium castaneum. Seventy-eight different fractions of petroleum ether extract were obtained from column chromatography. Elutes having the similar TLC behavior were combined in eight fractions and were named as: MN-1, MN-2, MN-3, MN-4, MN-5, MN-6, MN-7 and MN-8. Four separate fractions were collected from the MN-1 fraction by preparative thin layer chromatography. These four parts were washed with petroleum ether, chloroform, ethyl acetate and methanol. Thereafter, these were separated by small column and designated as: M1N1, M1N2, M1N3, M1N4, M2N1, M2N2, M2N3, M2N4, M3N1, M3N2, M3N3, M3N4, M4N1 and M4N2. Fractions of M1N2, M2N2, M3N2 and M4N2 were found to be the most effective against the beetle T. castaneum after 24, 48 and 72 hours. However, some fractions exhibited the moderate effect and other fractions did not work against the beetle. Bangladesh J. Sci. Ind. Res. 50(2), 143-152, 2015